Early silicone oil opacification in the absence of emulsification is caused by an increased level of silicone dioxide - Hammer, Maximilian; Britz, Leoni; Böhmann, Manuel Ben; Herbster, Lorenz; Muuß, Marcel; Herth, Jonathan; Cionoiu, Sebastian; Krisp, Holger; Spitzer, Martin; Wohlfart, Sabrina; Uhl, Philipp; Auffarth, Gerd U. (Retina, 2025)
Background/Purpose: -In October 2023, other cases with early silicone oil opacification within hours after intraocular implantation in the absence of emulsification occurred. Although multiple, small series of this phenomenon are now documented during the past decade, the cause was never unmasked. In this study, we analyzed explanted patient samples, unused samples of the affected, and a control batch of the same silicone oil. - Methods: - The oils were examined on their optical and viscosimetric properties, interfacial tension, and for the presence of particles. Contamination was investigated using inductively coupled plasma mass spectrometry, thermogravimetric analyses, and Raman spectroscopy. Cytotoxicity examination in ARPE-19 cells was performed. The oil's effect on pH changes of aqueous solutions and the oil's defoaming ability were analyzed. - Results: - The affected batch passed all regulatory limits. However, the affected batch showed an elevated turbidity already before implantation. Three thousand-fold magnification revealed dispersed particles only in the affected batch. Contamination analyses revealed the absence of other elements, indicating a silicon-containing contamination. The affected batch showed no in vitro cytotoxicity but altered viscosimetric properties and a lower pH of the hydrophilic phase after inducing emulsification. Both batches did not show relevant defoaming properties. - Conclusion: - The results obtained combined with information from suppliers and the manufacturer suggest an elevated level of silica particles as the cause of the opacification. Based on these results, the manufacturer and suppliers of the latest affected batch adjusted cutoff values for turbidity measurements and introduced turbidity measurements of the raw material before distillation. Other manufacturers should follow these preventive measures.